2021
DOI: 10.1038/s41598-020-79163-8
|View full text |Cite
|
Sign up to set email alerts
|

The pineapple MADS-box gene family and the evolution of early monocot flower

Abstract: Unlike the flower of the model monocot rice, which has diverged greatly from the ancestral monocot flower, the pineapple (Ananas comosus) flower is more typical of monocot flowers. Here, we identified 43 pineapple genes containing MADS-box domains, including 11 type I and 32 type II genes. RNA-seq expression data generated from five pineapple floral organs (sepals, petals, stamens, pistils, and ovules) and quantitative real-time PCR revealed tissue-specific expression patterns for some genes. We found that AcA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 65 publications
1
31
1
Order By: Relevance
“…These traits controlled by major genes include the distribution of spines and flower color. Both characters are controlled by 1-2 genes (Hu et al 2021). Furthermore, Burhooa & Ranghoo-Sanmukhiya (2012) reported that leaf shape and fruit shape could clearly distinguish pineapples.…”
Section: Accessions Identificationmentioning
confidence: 99%
“…These traits controlled by major genes include the distribution of spines and flower color. Both characters are controlled by 1-2 genes (Hu et al 2021). Furthermore, Burhooa & Ranghoo-Sanmukhiya (2012) reported that leaf shape and fruit shape could clearly distinguish pineapples.…”
Section: Accessions Identificationmentioning
confidence: 99%
“…These characteristics may allow alfalfa to adapt to diverse environments. In different geographic alfalfa groups (corresponding to the top 1% tail of Tajima's D values), we found several phenology-related genes (Figure 3C), including Msa0206730 (MsKNOX1, MsG0280008879 in Zhongmu No.1 genome), Msa0876740 (MsMADS20-1, MsG0680030394), Msa0876740 (MsMADS20-2, MsG0680030395) and Msa0868930 (MsMYB, MsG0680030409) which have been shown to be associated with plant growth, development, and flowering (Nishii et al, 2017;Hu et al, 2021;Naik et al, 2021;Pelayo et al, 2021).…”
Section: Selection Footprints Of Alfalfa Breedingmentioning
confidence: 99%
“…Recent studies in conserved ABCDE MADS-box genes in pineapple have been identified and are homologous to ABCDE floral development model in Arabidopsis sp., rice, and Antirrhinum sp.. Two A-class genes were identified from pineapple, AcFUL1 and AcFUL2. AcFUL1 have similarity with FUL-like I rice genes such as OsMADS15 and OsMADS14, and AcFUL2 is similar to FUL-like II rice genes such as OsMADS18 and OsMADS20 [12]. Volume The MADS-box gene characterization from oil palm identified 12 genes, of them EgSQUA1, EgSQUA2, and EgSQUA3 which are SQUAMOSA subfamily of Class A genes.…”
Section: Introductionmentioning
confidence: 97%
“…Although not all MADS-box genes are homeotic, they can act as meristem identity genes. ABC model was a new approach towards flower initiation proposed in 1991 to make clear the ability of homeotic genes in the organ identity of a flower suggests that the organ identity in each flower whorls is determined by a unique companies activity of three organ identity genes [12]. The ABC model was subsequently expanded to the ABCDE model [3][4][5][13][14][15].…”
Section: Introductionmentioning
confidence: 99%